Cardiac magnetic resonance imaging parameters show association between myocardial abnormalities and severity of chronic kidney disease - Jia, Xi; Han, Xiaoyu; Wang, Yuqin; He, Fangfang; Zhou, Xiaoyue; Zheng, Yuting; Guo, Yingkun; Xu, Rong; Liu, Jia; Li, Yumin; Gu, Jin; Cao, Yukun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Chronic kidney disease patients have increased risk of cardiovascular abnormalities. This study investigated the relationship between cardiovascular abnormalities and the severity of chronic kidney disease using cardiac magnetic resonance imaging. Methods We enrolled 84 participants with various stages of chronic kidney disease (group I: stages 1-3, n=23; group II: stages 4-5, n=20; group III: hemodialysis patients, n=41) and 32 healthy subjects. The demographics and biochemical parameters of the study subjects were evaluated. All subjects underwent non-contrast cardiac magnetic resonance scans. Myocardial strain, native T1, and T2 values were calculated from the scanning results. Analysis of covariance was used to compare the imaging parameters between group I-III and the controls. Results The left ventricular ejection fraction (49% vs. 56%, p = 0.021), global radial strain (29 vs. 37, p = 0.019) and global circumferential strain (-17.4 vs. -20.6, p < 0.001) were significantly worse in group III patients compared with the controls. Furthermore, the global longitudinal strain had a significant decline in group II and III patients compared with the controls (-13.7 and -12.9 vs. -16.2, p < 0.05). Compared with the controls, the native T1 values were significantly higher in group II and III patients (1041±7 and 1053±6 vs. 1009±6, p < 0.05), and T2 values were obviously higher in group I-III patients (49.9±0.6 and 53.2±0.7 and 50.1±0.5 vs. 46.6±0.5, p < 0.001). The advanced chronic kidney disease stage showed significant positive correlation with global radial strain (r = 0.436, p < 0.001), global circumferential strain (r = 0.386, p < 0.001), native T1 (r = 0.5, p < 0.001) and T2 (r = 0.467, p < 0.001) values. In comparison with the group II patients, hemodialysis patients showed significantly lower T2 values (53.2±0.7 vs. 50.1±0.5, p = 0.002), but no significant difference in T1 values (1041±7 vs. 1053±6). Conclusions Our study showed that myocardial strain, native T1, and T2 values progressively got worse with advancing chronic kidney disease stage. The increased T1 values and decreased T2 values of hemodialysis patients might be due to increasing myocardial fibrosis but with reduction in oedema following effective fluid management.